Ismeretlen adattörmelékek a 17. század második felének unitárius iskolaés peregrinációtörténetéhez - Szigeti Molnár, Dávid (Studia Litteraria, 2026)
The Unitarian College of Cluj (Kolozsvár), the sole Antitrinitarian institution to sponsor students’ peregrination, saw a significant setback in the early 1660s (due to a combination of fire damage, the bubonic plague, and an erosion of discipline). As a result, Unitarian peregrination temporarily “showed a tendency of decline”. From the 1670s, however, Unitarian students were again regularly sent to study abroad at the expense of the parish of Cluj, but before they left, the peregrines had to issue a pledge, a so-called promissory note (reversalis, obligatoria) to the ecclesia, pledging faithfulness and obedience, primarily; a practice also known in other denominations. These notes are usually – and correctly – regarded as formulaic in nature, but they contain the occasional interesting detail, such as the amount of the “scholarship” granted, the duration of enrolment and the required languages to be learned by the sponsored student. This study offers a systematic overview of these details.